Replacement of fish meal by poultry by-product meal, corn gluten meal and soybean meal in the diets of seabass (Lates calcarifer) fingerlings - Hoang, Thanh Hai (University of the Philippines in Visayas, 2009)
This study aimed to assess the replacement 40% protein of fish meal (in the Control Diet0 with soybean meal, corn gluten meal, poultry by-product meal and a mixed protein (in a 1.5:1: 2.5 ratio) in the diets of Asian seabass (Lates calcarifer). Five experimental diets were formulated to meet the about 49% dietary protein of seabass. The control diet contained Danish fish meal as the sole protein source. One hundred fifty fish with initial body weight 4.59 + 0.29g were randomly assigned to fifteen rectangular glass aquaria of 451 capacity and fed twice daily for 8 weeks. No water problem was experienced during the experiment, all water parameters were within acceptable range. In comparison with initial lipid content (4.99%), feeding seabass with testresulted in high lipid levels (19.69-22.93%) while crude protein increased slightly at the end of experiment. There was a downward trend in ash and moisture contents in the final body of seabass. There were no significant differences between the control diet and the mixed protein diet in terms of percentage weight gain (%WG), specific growth rate (SGR) and protein efficiency ratio (PER). The %WG (498.9 + 27.1) and SGR (3.2 + 0.08) were highest in fish fed the control diet and lowest (347.1 + 24.6) and (2.7 + 0.1) in those fed the poultry by-product diet. Similar trends were observed in protein efficiency ratio (PER), protein retention (PR) and condition factr (CF). The feed conversion ration (FCR) was influenced by the different dietary treatments. Feeding seabass with the control diet resulted in the significantly lowest FCR compared with those fed other test diets. Seabass fed the poultry by-product diet exhibited the highest FCR and was significantly different from those fed the control diet, soybean diet and mixed protein diets but not from those fed the corn gluten diet, Survival of seabass in all treatments ranged from 93.3 to 100%. The results did not show any remarkable difference between the control diet and the mixed protein diet on hepatosomatic index (HIS) and viscerasomatic (VSI) of seabass juvenile. Results from the present study demostrated that the mixed protein diet which replaced 40% fish meal protein could be applied to feed to juvenile seabass without adverse effects on growth, body composition and it was also nutritionally adequate and economical.